Consumer Perceptions of Chicken and Catfish Livestock Products with BSF Maggot Feed in Sekaran Village, Lamongan Regency, East Java - Dahlan, Mufid; Rusminah, Sani; Wahyuni, Wahyuni; Fadlilah, Anik; Khitam, Muhammad Chusnul; Putri, Marsha Savira Agatha; Laili, Fajriyah Kurnia (Universitas Halu Oleo, 2023)
Sekaran Village in overcoming the waste problem by forming TPS3R. An alternative to overcome this waste problem is cultivating maggot, which is used as fodder for chickens and catfish. This study aims to examine the effect of consumer perceptions on chicken and catfish purchasing decisions as a result of feeding maggots. The subject of this research is the people of Sekaran Village, with a sample of 100 people. The analysis used in this study uses index transformation analysis and partial t-test using SPSS 23. The analysis results of individual factor index transformation are 70.73%, stimulus factor is 71.58%, attitude is 55.23%, interest is 71.58%, and motivation is 69.46%. Based on the partial t-test analysis results, the individual factor indicator has a value of 6,930 > 1,985. The stimulus factor indicator has a value of 2,804 > 1,985. The attitude indicator is 4,785 >1,985, the interest indicator is 7,320 > 1,985, and the motivations are 6,184 > 1,985. Keywords: consumer perception, decision purchase, maggot BSF, TPS3R